Characteristics and survival of adult Swedish PAH and CTEPH patients 2000–2014. (3rd July 2016) - Rådegran, Göran; Kjellström, Barbro; Ekmehag, Björn; Larsen, Flemming; Rundqvist, Bengt; Blomquist, Sofia Berg; Gustafsson, Carola; Hesselstrand, Roger; Karlsson, Monica; Kornhall, Björn; Nisell, Magnus; Persson, Liselotte; et al.
Abstract: Objectives: The Swedish Pulmonary Arterial Hypertension Register (SPAHR) is an open continuous register, including pulmonary arterial hypertension (PAH) and chronic thromboembolic pulmonary hypertension (CTEPH) patients from 2000 and onwards. We hereby launch the first data from SPAHR, defining baseline characteristics and survival of Swedish PAH and CTEPH patients. Design: Incident PAH and CTEPH patients 2008–2014 from all seven Swedish PAH-centres were specifically reviewed. Results: There were 457 PAH (median age: 67 years, 64% female) and 183 CTEPH (median age: 70 years, 50% female) patients, whereof 77 and 81%, respectively, were in functional class III–IV at diagnosis. Systemic hypertension, diabetes, ischaemic heart disease and atrial fibrillation were common comorbidities, particularly in those >65 years. One-, 3- and 5-year survival was 85%, 71% and 59% for PAH patients. Corresponding numbers for CTEPH patients with versus without pulmonary endarterectomy were 96%, 89% and 86% versus 91%, 75% and 69%, respectively. In 2014, the incidence of IPAH/HPAH, associated PAH and CTEPH was 5, 3 and 2 per million inhabitants and year, and the prevalence was 25, 24 and 19 per million inhabitants. Conclusion: The majority of the PAH and CTEPH patients were diagnosed at age >65 years, in functional class III–IV, and exhibiting several comorbidities. PAH survival in SPAHR was similar to other registers.